The Role of Multicultural Education in Enhancing Students' Tolerance in Secondary Schools - Ahmad Fauzi (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2025)
Multicultural education is an important approach in building social harmony amidst the diversity of ethnicities, religions, and cultures in Indonesia. This study aims to analyze the contribution of multicultural education to increasing the tolerance of high school students. The research method used is qualitative with a case study approach in two public schools in Yogyakarta that have heterogeneous student backgrounds. Data were collected through classroom observations, in-depth interviews with teachers and students, and analysis of curriculum documents. The results of the study indicate that the integration of multicultural values ​​in learning, culture-based extracurricular activities, and teacher training have a positive impact on increasing attitudes of mutual respect among students. Consistent implementation and support from all school components are key factors in creating an inclusive educational environment. These findings contribute to the development of educational policies that are responsive to social and cultural diversity.